1999
DOI: 10.1053/rmed.1999.0579
|View full text |Cite
|
Sign up to set email alerts
|

Familial sarcoidosis in Finland and Hokkaido, Japan–a comparative study

Abstract: Two or more cases of sarcoidosis in one family is not unusual. To compare the frequencies of familial sarcoidosis in Finland and Hokkaido, Japan, and to analyse the type of associations reported, we collected data on all patients visiting hospitals for sarcoidosis in 1984 in Finland (1378 patients) and Hokkaido (208 patients), including information about familial sarcoidosis. We also analysed the familial cases seen among 571 sarcoidosis patients diagnosed at the Mjölbolsta hospital in Finland from 1955 to 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1
14

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 13 publications
5
112
1
14
Order By: Relevance
“…In this Irish study, 9.6% of index cases were found to have at least one sibling with sarcoidosis. In a comparative study in Finland and Hokkaido, Japan, prevalence of familial sarcoidosis was comparable, being 3.6±4.7% in Finland and 2.9±4.3% in Hokkaido [35], in spite of the marked difference of overall prevalence of the disease between the two regions (28.2 versus 3.7 per 100,000, respectively) [15].…”
Section: Familial Aggregation Of Sarcoidosismentioning
confidence: 91%
See 1 more Smart Citation
“…In this Irish study, 9.6% of index cases were found to have at least one sibling with sarcoidosis. In a comparative study in Finland and Hokkaido, Japan, prevalence of familial sarcoidosis was comparable, being 3.6±4.7% in Finland and 2.9±4.3% in Hokkaido [35], in spite of the marked difference of overall prevalence of the disease between the two regions (28.2 versus 3.7 per 100,000, respectively) [15].…”
Section: Familial Aggregation Of Sarcoidosismentioning
confidence: 91%
“…yr -1 for males and 6.3 for females [13], whereas an annual all-race incidence rate of 4.8 per 100,000 persons was estimated in a Northwest US population [14]. In a comparative study, the prevalence of sarcoidosis in Finland was 28.2 per 100,00 and 3.7 per 100,000 in Japan (Hokkaido area) [15]. Studies in homogeneous areas have shown marked racial variations.…”
Section: Relationship Between Genetic and Environmental Factors Affecmentioning
confidence: 99%
“…Familial sarcoidosis is mostly seen in siblings, then in mother-child relationships, and less frequently in father-child relationships (11,12). Its prevalence is high in monozygotic twins and in the same race, which suggests that the disease has a genetic component (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…There were eight sibling-sibling, three mother-daughter, one mother-son, one father-son, and one cousin-cousin sarcoidosis cases in the study. No difference was found between familial sarcoidosis and non-familial sarcoidosis with regard to clinical presentation and prognosis (11,17). Sarcoidosis is a disease that is often seen in young adolescents and women (18).…”
Section: Discussionmentioning
confidence: 99%
“…Following the first description of 2 German sisters with sarcoidosis, the studies examining the familial clustering of the disease in various populations have reported 2.7%-17% of index cases with another affected family member (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%